Genome‐wide gene expression in a pharmacological hormonal transition model and its relation to depressive symptoms. (24th May 2019) - Mehta, D.; Rex‐Haffner, M.; Søndergaard, H. B.; Pinborg, A.; Binder, E. B.; Frokjaer, V. G.
Abstract : Objectives: Sensitivity to sex‐steroid hormone fluctuations may increase risk for perinatal depression. We aimed to identify genome‐wide biological profiles in women demonstrating sensitivity to pharmacological sex‐hormone manipulation with gonadotrophin‐releasing hormone agonist (GnRHa). Methods: Longitudinal gene expression (Illumina Human HT12.v4) and DNA methylation data (Infinium HumanMethylation450K BeadChip) from 60 women (30 GnRHa, 30 placebo) were generated (Trial ID: NCT02661789). Differences between baseline and two follow‐up points (initial stimulation‐ and subsequent early suppression phase) in the biphasic ovarian hormone response to GnRHa were assessed using linear mixed effects models. Results: Genome‐wide analysis revealed 588 probes differentially expressed from GnRHa intervention to first stimulatory phase follow‐up (intervention group × time) after 10% fdr multiple testing correction. Of these, 54% genes were also significantly associated with estradiol changes over time (proxy for GnRHa response magnitude), 9.5% were associated with changes in depressive symptoms, and 38% were associated with changes in neocortical serotonin transporter binding. The genes were implicated in TGF beta signaling, adipogenesis, regulation of actin cytoskeleton, and focal adhesion pathways and enriched for DNA methylation changes ( P  = 0.006). Conclusions: These findings point toward an altered peripheral blood transcriptomic landscape in a pharmacological model of sex‐hormone‐induced depressive symptoms.